Future prospects of interdependence among East Asian economies - Komiya, Ryutaro 1928-; Ashakul, Charuma; Bhongmakapat, Teerana; Tsusho Sangyosho Tsusho Sangyo Kenkyujo (Japan); Chulalongkonmahawitthayalai. Sun Wichai Setthasat; International conference on'Future Prospects of Interdependence among East Asian Economies' 91993 : Bangkok, Thailand) ([Bangkok] : Chulalongkorn University Printing House, 1994)
Papers presented at International Conference on'Future Prospects of Interdependence among East Asian Economies' organized by Research Institute of International Trade and Industry, Ministry of International Trade and Industry, Japanese government and Chulalongkorn Economics Research Center, Faculty of Economics, Chulalongkorn University, 3-4 February 1993, Bangkok, Thailand
'September 1994, MITI & CERC.'
Includes bibliographical references
Keywords: East Asia -- Economic policy -- Congresses